Analisis Keterampilan Passing Kaki Bagian dalam pada Permainan Sepak Bola Pemain Massenrempulu FC Kabupaten Enrekang - Wahyu; Maria Ulfah; Abd. Malik Sirfa; Ronaldi; Andi Arfiana; Juhanis; Poppy Elisano Arfanda (Indo-MathEdu Intellectuals Journal, 2026)
This study aims to determine the level of inside-foot passing skills in football among players of Massenrempulu FC in Enrekang Regency. The study employed a quantitative approach using a descriptive method. The study population consisted of 73 players, whilst the sample comprised 30 players. Data collection was carried out through an inside-foot passing skills test and observation sheets. The data obtained were analysed using descriptive statistics with the aid of SPSS version 20.00. The results of the study showed that 22 players (73%) were in the ‘very good’ category, 7 players (23%) in the ‘good’ category, and 1 player (4%) in the ‘average’ category, whilst no players were in the ‘poor’ or ‘very poor’ categories. Based on these results, it can be concluded that the inside-foot passing skills of Massenrempulu FC players from Enrekang Regency are classified as very good with an average score of 9.03, meaning that the players’ basic passing ability meets the expected skill criteria in football.